Теоретичні та експериментальні дослідження гідравлічних пружин - Калініченко, Володимир Якович; Kalinichenko, Volodymyr; Коваленко, Володимир Васильович; Kovalenko, Volodymyr (Дніпровський державний аграрно-економічний університет, 2014)
Усі відомі типи гідравлічних амортизаторів мають постійну характеристику, оскільки опір розтягненню залежить тільки від зовнішньої сили. Запропоновано нову схему амортизатора Е3000, в якому сила опору може змінюватися, що забезпечується переміщенням поршня-дозатора, який знаходиться всередині основного поршня. При переміщенні поршня-дозатора збільшується довжина кільцевої щілини, чому і збільшується гідравлічний опір амортизатора. In hydraulic springs that are used as shock absorbers, provided as a damping suppression of compressed energy fluid, it equipped with spring damper in the form of throttle unilateral or bilateral action .Damping energy (throttling fluid) occurs either by direct course (compression springs), or reverse course (when straightening spring). Or both at the same time forward and reverse course. Common are the second type of hydraulic springs, which occur in the course of direct potentiation of almost pure energy fluid which is compressed, it is damping occurs when straightening the spring.All known types of hydraulic shock absorbers with constant characteristic impedance strain depend on the external force. A new scheme damper E3000, which can vary the resistance provided by the movement of the piston – dosing, which is in the middle of the main piston. When you move the piston dosing increases the length of the ring gap and, therefore, increases the hydraulic resistance of the shock absorber.Calculations were performed to determine the optimal ratio between the sizes of the hydraulic damper elements: their diameter inlet and main channel width annular gap and the top diameter of the piston dosing. Obtained by calculating the resistance depends on the parameters of the hydraulic damper elements, and the value of the external load.Calculations and test prototypes showed that the shock variable resistance can develop resistance to tensile strength and 70 % of the value of the external force acting on the suspension of the car. Thus, when working on the topic developed a mathematical model of hydraulic shock absorber set up a program of key parameters similar hydraulic springs.
Theoretical and experimental study of hydraulic springs
Keywords: гідравлічні пружини; hydraulic springs; амортизатор; shock absorbers; ударні перевантаження; shock overload; сила опору; resistance force; буферні прилади; buffering device; закон Гука; Hooke’s law; дросель; throttle; демпфірування енергії; damping energy; потенціювання енергії; potentiation energy; деаерована рідина; deaerated liquid